Do Akhbār Mulūk al-Andalus [Notícias dos Monarcas da Hispânia] à Crónica do Mouro Rasis - António Rei (Medievalista)
A work and a myth, whose journey began in the 10th century, in the Califal Chancellery of Córdoba, during the reign of ‘Abd al-Raḥmān III, and whose contents and information are still valid today and giving rise to several and varied studies. A work to which a name is linked, “al-Rāzī”, whose Latinized version, “Rasis”, ended up being glued to the first translation into Portuguese, which since the 13th century began to transmit that memory, and then to the translation of the Portuguese version into Castilian, where it settled. The text that served as the basis for that first Portuguese translation, and from which that attribution to “Rasis” arose, was already, in fact, the work of Ibn Ġālib, a 12th century recast. The text of the first translation passed through several hands, places and situations until it disappeared in the earthquake of 1755. The Castilian translation and the Crónica General de Espanha of 1344, which had the former as its source, allowed us to reconstruct the text of the lost translation. Throughout the 19th and 20th centuries, editions and translations of Arabic texts raised the idea of ​​a possible recreation of the lost Arabic matrix.